Yield Assessment and Financial Analysis of Azadirechta indica A. Juss. Var. Siamensis Valeton in Prachuap Khiri Khan Silvicultural Research Station, Prachuap Khiri Khan Province: การประเมินผลผลิตและการวิเคราะห์ทางการเงินของไม้สะเดา ในสถานีวนวัฒนวิจัยประจวบคีรีขันธ์ จังหวัดประจวบคีรีขันธ์ - Jareonvong, Kamonpat; Suksard, Santi; Jarusombuti, Songklod; Sriarkarin, Supasit; Chuntachot, Chanittha (Journal of Applied Economics and Management Strategy, 2022)
บทคัดย่อ การศึกษาครั้งนี้มีวัตถุประสงค์เพื่อหาสมการปริมาตรของไม้ที่ทำเป็นสินค้าได้ สมการปริมาตรไม้ฟืนของไม้สะเดา และวิเคราะห์ทางการเงินจากการปลูกไม้สะเดา ณ สถานีวนวัฒนวิจัยประจวบคีรีขันธ์ โดยใช้ตัวชี้วัดความเหมาะสมของโครงการ 3 ค่า คือ มูลค่าปัจจุบันสุทธิ (NPV) อัตราส่วนผลตอบแทนต่อต้นทุน (B/C) และ อัตราผลตอบแทนภายใน (IRR) ณ อัตราส่วนลด 6, 8, 10 และ 12 อายุโครงการ 25 ปี ผลการศึกษาพบว่าสมการปริมาตรไม้ที่ทำเป็นสินค้าได้ และ สมการปริมาตรไม้ฟืนของไม้สะเดาที่มี DBH มากกว่า 10 เซนติเมตร คือ VM = 0.000008DBH2.068824H1.342000 และ VF>10 = 0.395947 + 0.000960DBH2 - 0.038916DBH ตามลำดับ และสมการปริมาตรไม้ฟืนของไม้สะเดาที่มี DBH น้อยกว่าหรือเท่ากับ 10 เซนติเมตร คือ VF≤10 = - 0.011195 + 0.000609DBH2 ปริมาตรไม้ที่ทำเป็นสินค้าได้เฉลี่ย และปริมาตรไม้ฟืนเฉลี่ยของไม้สะเดาเท่ากับ 18.6216 และ 5.2478 ลูกบาศก์เมตร/ไร่ ตามลำดับ การวิเคราะห์ทางการเงินของผลผลิตเฉลี่ยของไม้สะเดา ณ อัตราส่วนลด 6, 8, 10 และ 12 พบว่า NPV มีค่าน้อยกว่า 0 B/C มีค่าน้อยกว่า 1 และ IRR มีค่าน้อยกว่าอัตราส่วนลดที่กำหนด แสดงว่าการปลูกไม้สะเดาขาดทุน ดังนั้นการลงทุนปลูกสร้างสวนป่าไม้สะเดาเพื่อทำไม้แปรรูปไม่เหมาะสมแก่การลงทุนเพื่อปลูกสร้างสวนป่าไม้เศรษฐกิจ ABSTRACT The objectives of this study were to examine the merchantable volume equation, firewood volume equation and financial analysis of Azadirechta indica A. Juss. Var. Siamensis or Siamese neem tree grown at Prachuap Khiri Khan Sivicultural Research Station. Using suitable indicators under 3 criteria as follows: (1) net present value (NPV), (2) benefit-cost ratio (B/C) and (3) internal rate of return (IRR) at the given discount rate of 6, 8, 10 and 12 % in a 25-year life project. The results of this study revealed that using for estimating merchantable volume equation and firewood volume equation of the Siamese neem tree with DBH more than 10 centimeters were VM = 0.000008DBH2.068824H1.342000 and VF>10 = 0.395947 + 0.000960DBH2 - 0.038916DBH, respectively. Estimating firewood volume equation of the Siamese neem tree with DBH less than or equal to 10 centimeters was VF≤10 = - 0.011195 + 0.000609DBH2. Average merchantable volume and firewood volume of Siamese neem tree were 18.6216 and 5.2478 m3/rai, respectively. Financial analysis of average yields Siamese neem tree at the given discount rate of 6, 8, 10 and 12 % have NPV < 0, B/C < 1 and the IRR less than determinated discount rate indicating the loss of this project. Thus, the investment of Siamese neem tree plantation for timber product was not suitable as economic plantation project.